Excavations in Midea 2007 - Demakopoulou, Katie; Divari-Valakou, Nicoletta; Nilsson, Monica; Schallin, Ann-Louise (Opuscula. Annual of the Swedish Institutes at Athens and Rome, 2009)
Excavations in Midea continued in 2007 as a Greek-Swedish programme under the direction of Dr Katie Demakopoulou in collaboration with Dr Ann-Louise Schallin. In the West Gate area excavation continued in the west part of the building complex that abuts the fortification wall. Room XIV was excavated with abundant remains of LH IIIB2 pottery. A sealstone with a unique, possibly ritual, scene was also found. On the lower west terrace of the acropolis excavation continued in Trench C, where a large section of the fortification wall was uncovered. Room I was excavated here, adjacent to the inner face of the fortification wall. Finds in this room date to the early phase of LH IIIC, under which there was ample evidence of the LH IIIB2 destruction, including human skeletons. Under this debris, a large opening leading to a gallery or syrinx through the thickness of the fortification wall was found. Excavation was resumed also in the East Gate area, where a new wall was revealed in the baulk between Trench 3 and Room 9. The wall is perpendicular to the citadel wall and borders Trench 3. Excavation was also resumed in Trenches 9 and 14. The latest Mycenaean material in this area dates to LH IIIB2, but there is evidence of post-Bronze Age activity, which is demonstrated mainly by pottery finds.